Governance milieus in shrinking post-socialist city regions and their respective forms of creativity. Case miniatures and conceptual propositions. - Matthiesen, Ulf (TH Zürich, ORL-Institut, 2005)
Anhand der an der polnischen Grenze gelegenen brandenburgischen Städte Forst, Guben, Frankfurt/Oder zeigt der Beitrag drei unterschiedliche kreative städtische Antworten auf die dramatischen postsozialistischen Schrumpfungsprozesse und die Entwicklungen durch die EU-Osterweiterung. Konzeptionell wird dabei das analytische Instrument des Governance-Milieus eingeführt, das für das Wahrnehmen tatsächlichen Netzwerkeffekte der neuen Governance-Ansätze tauglich ist. Auf die Zusammenhänge von Wissen und Kreativität wird hingewiesen, zwischen "weichen" Wissensmilieus, "harten" Wissensnetzen und heterogenen Wissenskulturen wird unterschieden. Zusammengenommen lassen sich drei verschiedene Arten von Governance-Kreativität unter den Bedingungen von Schrumpfung ausmachen. oc/difu

Creative approaches to governance seem to be particularly context-dependent. Whether a city region is growing, stagnating or shrinking makes a big difference here. In the article, the normative-analytical concept of governance creativity will be tackled from the shrinkage side of city-regional developments in order to make this context dependency of governance approaches a bit more intelligible. Three case miniatures from East-German industrial cities situated on the German-Polish border serve as the material basis for the argumentation (Forst, Guben-Gubin, Frankfurt/Oder). These ease miniatures include sketches of three ease-specific approaches to creatively overcoming the heavy shrinkage effects of transformational path-dependencies. On the conceptual side, an analytical tool of governance milieus is introduced in order to adequately focus the factually realized network effects stemming from new governance approaches. Special focus is placed on the interrelations between knowledge and creativity. The distinction between "soft" knowledge milieus, "hard" knowledge networks and heterogeneous knowledge cultures is introduced. "Played together", these structural layers give rise to three different governance creativity types under shrinkage conditions. This may also throw some light on stagnating and growing city regions and their creative governance options as well. difu
Keywords: Stadtentwicklungsplanung; Schrumpfung; Innovation; Planungstheorie; Strukturwandel; Innovation; Hochschule; Grenzraum; Transformationsprozess; Governance; Kreativität; Urban Governance; Local Governance; Wissensgesellschaft; Wissen; Fallbeispiel; Grenzstadt; Stadtumbau